Truth commission testimony : relation to psychiatric status and forgiveness among South African survivors of human rights violations - Kaminer, Debra (Department of Psychology, 2014)
The present study aimed to examine the degree to which giving TRC testimony is related to current psychiatric status and forgiveness attitudes among survivors of human rights abuses. A literature review examined the degree to which the TRC's claims are supported by the existing theoretical and empirical literature on trauma narratives and on forgiveness, and guided the way that psychological outcomes were assessed in the current study. Sunivors (n=134) who gave public, private or no testimony to the TRC completed standardised instruments measuring demographic variables, exposure to human rights abuses, current psychiatric status and forgiveness attitudes towards the perpetrator(s).